MARGIN DAN STRATEGI PEMASARAN KOMODITI JAGUNG DI KABUPATEN GORONTALO - Indrianti, Merita Ayu (Jurnal Social Economic of Agriculture, 2020)
This research was conducted at Gorontalo district. The objective of this research is how the marketing margins and the marketing strategy of corn commodity at Gorontalo district. The result of the marketing margin that first (I) line has the big marketing margin Rp. 1.300 because the marketing line done by direct marketing. While for the low marketing margins contained on line III with margin Rp. 0, because marketing in line III is the indirect marketing. From the result of analysis internal and external factor SWOT strategy that can be developed in corn marketing at Gorontalo district is diversification strategy that has value X = 0,04 and Y = 0,36. Therefore strategy that recommended based on the priority scale are: 1). Facilitate the farmer to be able in access banking credit. 2). Motivate the farmer to more improve to farm the corn. 3). Provide coaching the technology of maize cultivation and post harvest handling.Keywords: Strategy, Marketing of Corn Commodity